Mamíferos de médio e grande porte em corredores de matas ripárias e de valos no sul de Minas Gerais - Vilas Boas Junior, Flávio Eduardo (2019)
Land use change and occupation has leading to process of fragmentation and loss of habitat, causing enormous pressure on biodiversity. These processes compromise the persistence of populations in altered environments, leading to the extinction of species and their ecosystem services. Instrument such as ecological corridors are proposed to mitigate the problems caused by fragmentation, because they allow the species to transit between the fragments, since the matrix of the surroundings can inhibit the movement of the species. It's known that vegetation corridors are important, however the width of these structures can be an important variable in its functionality, being necessary a width of 200 meters for sensitive species can use them. In landscape of south of Minas Gerais, two vegetation corridors are present in the landscape, Riparian Forests and Valos. Thus, the objective of this research was to evaluate how medium and large size mammals use these corridors to propose conservation measures for these species. We selected 20 corridors (10 Riparian Forests and 10 Valos), in two landscapes immersed in different matrices (pasture and coffee plantation). Sampling was done for 120 days at each point using câmera-trap. Our results showed that Riparian Forests are more rich, abundant and with different composition when compared to Valos, being width variable that best explained this difference. Although not significant, pasture matrix contributed negatively to richness of species, however, our landscapes did not differ in their richness, because pasture favored the appearance of opportunistic species. We conclude that both corridors are important for landscape, since we obtained registries of mammals at all points and the Valos, although with smaller width and with fewer records, large species were able to use them as was case of cougar. We also found a gradient between corridors, being the best model for species conservation are Riparian Forests in coffee matrix, followed by the Riparian Forests in pasture, Valos in coffee and Valos in pasture. Brazilian legislation considers Riparian Forests as APPs, however the width stipulated by law isn't based on fauna conservation. It's necessary increase the width of these areas, besides promoting an environmental education for population understand the need to maintain these areas and biodiversity that dependent on it.